Postmemory: Fragments / Crypt - Spatz, Ben; Cohen, Lxo; Dodd, Lindsey; Erçin, Nazlıhan Eda; Kolar, Paula; Mendel, Agnieszka (Performance Matters, 2023)
This photo essay gathers evidence of the video works Postmemory: Fragments and Postmemory: Crypt, which ran from June 27 to August 4, 2022, at Holocaust Centre North at the University of Huddersfield in northern England. Included here are photographs from the video works and their installation, as well as the complete exhibition program. In an accompanying statement, Spatz positions this work within the broader Judaica project, an extended investigation of contemporary jewish identity developed over the past decade, and in relation to the four themes suggested by the editors of this special issue: ethics, knowledge, affect, and power.